Preparation and Property Analysis of Flavonoids Microcapsules from Tartary Buckwheat Sprout - Shan HUANG; Hui LIU; Luona ZHOU; Yang LU; Jun LI; Changheng CHEN; Du LÜ; Mu PAN; Yong ZENG (Shipin gongye ke-ji, 2023)
To improve the stability and bioavailability of tartary buckwheat sprout flavanoids, microcapsules containing tartary buckwheat sprout flavanoids (TBSF) were prepared according to spray drying process using carrageenan+modified starch, gum arabic (GA)+modified starch, maltodextrin (MD)+modified starch+gelatin as the wall materials. The structure and antioxidant activity of TBSF microcapsules were analyzed by measuring the water content, repose angle, hygroscopicity, DPPH and ABTS+ free radical scavenging capacity of microcapsules. The results indicated that the microcapsule prepared from carrageenan+modified starch showed best performance, which possessed lowest water content (6.58%), largest bulk density and smallest repose angle (13.20°), best fluidity, slowest hygroscopicity change, highest scavenging capacity of DPPH and ABTS+ free radicals, as well as highest uniformity with full and spherical surface. The embedding rate of GA+modified starch and MD+modified starch+gelatin microcapsules were 82.21% and 82.72%, respectively. Compared to carrageenan+modified starch, these two kinds of microcapsules displayed relative low antioxidant capacity, poor moisture absorption stability, large pores on the particle surface and worse uniformity. The fourier transform infrared spectroscopy analysis showed that three kinds of microcapsules contained characteristic absorption peaks of flavonoids. The release performance of three kinds of microcapsules in simulated intestinal fluid were all better than in simulated gastric juice, implied that the core materials (flavanoids) in microcapsules were mainly conducive to be released in the intestine and functioned as antioxidants. Totally, carrageenan+modified starch was an ideal wall material for production of TBSF microcapsules. Results would be helpful to promote the microencapsulation of tartary buckwheat sprout flavanoids and its application in the field of functional food.